PENGARUH LAYANAN LOW COST CARRIER (LCC) TERHADAP KEPUASAN WISATAWAN DOMESTIK DI PT. INDONESIA AIRASIA - Tresia Silalahi, Agnes; Suardana, I Wayan; Susrami Dewi, Ni Gusti Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 4 No 2 (2016): Jurnal IPTA (December 2016)DO - 10.24843/IPTA.2016.v04.i02.p07)
AirAsia airline crash incident in December 2014 raises a big question to the satisfaction of the user rating AirAsia. Therefore, this study aims to determine: (1) the effect of partially Low Cost Carrier services to tourist satisfaction PT. Indonesia AirAsia; (2 effect of simultaneous service Low Cost Carrier to tourist satisfaction PT. Indonesia AirAsia. The samples in this study with a total sample of 110 respondents. The analysis used T-test & F-test. The results showed that partially, the influence of the Low Cost Carrier to satisfaction rating are the following results: (1) safety with the effect of -2.907, (2) no frills with the effect of 4.136, (3) distribution with the effect of 1.776, (4 ) price with the effect of 1,784 and (5) flight regularity with the effect of 2,134. With simultaneously shows that the influence is14.660. From the results it is known that variable safety is a variable that has no effect. This is due to security so low it felt absolutely no effect. This contrasts with study conducted by Clemes et al (2008) where safety is an important factor in the quality of aviation services, and security are the two most important attributes in flight .
Keywords: Low Cost Carrier, Customer Satisfaction